The occurrence of Toxocara malaysiensis in cats in China, confirmed by sequence-based analyses of ribosomal DNA - Li, Ming Wei; Zhu, Xing Quan; Lin, Rui Qing; Robin, Gasser B.; Abdullah Sani, Rehana; Lun, Zhao Rong; Dennis, Jacobs E. (Springer-Verlag, 2006)
Non-isotopic polymerase chain reaction (PCR)- based single-strand conformation polymorphism and sequence analyses of the second internal transcribed spacer (ITS-2) of nuclear ribosomal DNA (rDNA) were utilized to genetically characterise ascaridoids from dogs and cats from China by comparison with those from other countries. The study showed that Toxocara canis, Toxocara cati, and Toxascaris leonina from China were genetically the same as those from other geographical origins. Specimens from cats from Guangzhou, China, which were morphologically consistent with Toxocara malaysiensis, were the same genetically as those from Malaysia, with the exception of a polymorphism in the ITS-2 but no unequivocal sequence difference. This is the first report of T. malaysiensis in cats outside ofMalaysia (from where it was originally described), supporting the proposal that this species has a broader geographical distribution. The molecular approach employed provides a powerful tool for elucidating the biology, epidemiology, and zoonotic significance of T. malaysiensis.